Combined Analysis of MicroRNAs and Target Genes Revealed miR156-SPLs and miR172-AP2 Are Involved in a Delayed Flowering Phenomenon After Chromosome Doubling in Black Goji (Lycium ruthencium) - Rao, Shupei; Li, Yue; Chen, Jinhuan (Frontiers in Genetics, 2021)
Polyploidy, which is widely distributed in angiosperms, presents extremely valuable commercial applications in plant growth and reproduction. The flower development process of higher plants is essential for genetic improvement. Nevertheless, the reproduction difference between polyploidy and the polyploid florescence regulatory network from the perspective of microRNA (miRNA) remains to be elucidated. In this study, the autotetraploid of Lycium ruthenicum showed late-flowering traits compared with the progenitor. Combining the association of miRNA and next-generation transcriptome technology, the late-flowering characteristics triggered by chromosome duplication may be caused by the age pathway involved in miR156-SPLs and miR172-AP2, which inhibits the messenger RNA (mRNA) transcripts of FT in the leaves. Subsequently, FT was transferred to the shoot apical meristem (SAM) to inhibit the expression of the flowering integration factor SOC1, which can eventually result in delayed flowering time. Our exploration of the flowering regulation network and the control of the flowering time are vital to the goji producing in the late frost area, which provides a new perspective for exploring the intrinsic molecular mechanism of polyploid and the reproductive development of flowering plants.